2000
DOI: 10.1037/0012-1649.36.4.485
|View full text |Cite
|
Sign up to set email alerts
|

Connectedness and autonomy support in parent–child relationships: Links to children's socioemotional orientation and peer relationships.

Abstract: Connectedness and autonomy support in the parent-child relationship are constructs that emerge from object relations and attachment theories but that overlap with other commonly studied qualities of parent-child relationships to provide a unifying focus for research in this domain. In this study, these constructs were examined in relation to children's relational competence, including socioemotional orientation, friendship, and peer acceptance. Semistructured conversations between mothers and their 5-year-olds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
228
2
14

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(255 citation statements)
references
References 56 publications
(67 reference statements)
11
228
2
14
Order By: Relevance
“…Compared to childcare activities, play activities are characterized by higher levels of parental responsiveness, compliance and shared positive affect (Lindsey et al, 2010). These specific features of parental engagement style have been associated with children's prosocial behavior (BrophyHerb et al, 2010;Clark & Ladd, 2000;Lindsey et al, 2010). Therefore, the distinct types of parent-child activities may influence the association between the quality of the parent-child relationship and children's prosocial behavior, explaining differences between mothers' and fathers' contributions to children's prosocial behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to childcare activities, play activities are characterized by higher levels of parental responsiveness, compliance and shared positive affect (Lindsey et al, 2010). These specific features of parental engagement style have been associated with children's prosocial behavior (BrophyHerb et al, 2010;Clark & Ladd, 2000;Lindsey et al, 2010). Therefore, the distinct types of parent-child activities may influence the association between the quality of the parent-child relationship and children's prosocial behavior, explaining differences between mothers' and fathers' contributions to children's prosocial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies suggesting the association between children's prosocial behavior and distinct positive features of the parent-child relationship, namely parental involvement, warmth, responsiveness, sensitivity, connectedness, prosocial modeling and parental encouragement of children's emotional expression (Brophy-Herb et al, 2010;Bryant & Crockenberg, 1980;Clark & Ladd, 2000;Garner, 2006;Kärtner, Keller, & Chaudhary, 2010;Kiang, Moreno, & Robinson, 2004;Koestner, Franz, & Weinberger, 1990). In a 26-year longitudinal study, Koestner et al (1990) found early paternal involvement in child care to be significantly associated with empathic concern at the age of 31 years.…”
Section: Parental Relationships and Children's Prosocial Behaviormentioning
confidence: 99%
“…Specifically, research has identified that positive, early relationships between children and caregivers contribute to neural connections that facilitate children's long-term developmental success (National Scientific Council on the Developing Child, 2004). Children in more highly connected parent-child relationships tend to display more positive socioemotional outcomes, such as stronger prosocial orientations, more numerous and higher-quality friendships, and higher levels of peer acceptance in kindergarten (Clark and Ladd, 2000). Through connected interaction with parents, children appear to develop an empathic socioemotional orientation that serves as a foundation for interpreting social situations and responding more prosocially to age-mates and teachers.…”
Section: Parental Warmth and Sensitivitymentioning
confidence: 99%
“…Prosocial behavior, that is, behavior intended to help others [11], is known as the fundamental component of human relationships [12]. Prosocial children get on with other children and have better relationships than children who have lower in prosocial behavior [13].…”
Section: Introductionmentioning
confidence: 99%